2017
DOI: 10.1002/agr.21513
|View full text |Cite
|
Sign up to set email alerts
|

Financial behavior of cooperatives and investor‐owned firms: An empirical analysis of the Spanish fruit and vegetable sector

Abstract: A partial adjustment model was formulated to compare financial ratios between cooperatives and investor‐owned firms from a dynamic perspective. Empirical results from a sample of Spanish fruit and vegetable firms for the period between 2009 and 2012 reveal different adjustment processes of current, debt, and return on assets ratios between cooperatives and IOFs. We find significant differences between these firms, with slower adjustment rates for current and debt ratios in cooperatives. These findings may aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…While the difference between the financial cycle of both samples is not statistically significant (p-value 5 0.13), the self-funding rates of the groups proved to be different at the 1% level (p-value 5 0.00), indicating that it is the firms' capacity to provide resources from their operations (self-funding) that determines their ability to achieve sustainable growth. This evidence is consistent with the dual nature of cooperative firms (Valentinov and Iliopoulos, 2013;Martinez-Vict oria et al, 2018). As they can maximize members' interests through prices, agricultural firms have an incentive to operate with lower margins, thus benefiting the members, who are also providers/clients of their organizations.…”
Section: Short-term Financial Sustainabilitysupporting
confidence: 74%
See 2 more Smart Citations
“…While the difference between the financial cycle of both samples is not statistically significant (p-value 5 0.13), the self-funding rates of the groups proved to be different at the 1% level (p-value 5 0.00), indicating that it is the firms' capacity to provide resources from their operations (self-funding) that determines their ability to achieve sustainable growth. This evidence is consistent with the dual nature of cooperative firms (Valentinov and Iliopoulos, 2013;Martinez-Vict oria et al, 2018). As they can maximize members' interests through prices, agricultural firms have an incentive to operate with lower margins, thus benefiting the members, who are also providers/clients of their organizations.…”
Section: Short-term Financial Sustainabilitysupporting
confidence: 74%
“…Our results also indicated that this difference between the quality of growth in the two groups is due to the lower capacity of agricultural cooperatives to provide resources from their own operations (self-funding) in comparison with their publicly traded peers, leading them to fund their working capital needs with higher levels of debt. A possible explanation for this difference in financial performance is the dual characteristic of cooperative members (Valentinov and Iliopoulos, 2013;Martinez-Vict oria et al, 2018). Since, in addition to being owners, they are also clients and suppliers, the results due to the growth in sales could be distributed to them through prices, lowering the operational margins of coops, causing the stagnation (or even deterioration) of their financial sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial ratio analysis is used for comparative purposes too (e.g., industry-specific sector comparisons) [72,73]. Strikingly, a large body of work comparing the performance of cooperatives with that of IOFs in the same sector(s) (e.g., dairy, grain, farm supply) is present (e.g., [73][74][75][76][77][78][79][80]). Moreover, some studies (e.g., [81][82][83]) employ sales-based metrics (e.g., market shares, sales growth, the Lerner index) next to financial ratios to paint a more complete picture of financial measures and cooperative performance.…”
Section: Preliminary Frameworkmentioning
confidence: 99%
“…At present, however, there remains a scarcity of research that is suitable for practical decisions about whether a company is at risk and should tackle the potential crisis [13]. There are several authors who have examined the financial health of agricultural companies, including Kravčáková Vozárová et al [14][15][16], Valašková et al [17], Adamišin et al [18], Hornungová and Milichovský [19], Henning and Jordaan [10], Martínez-Victoria et al [20], Sjauw-Koen-Fa et al [21], Lopez-Valeiras et al [22], Majewski [23], and Soboh et al [24]. However, there remains a scarcity of studies that engage in designing a systematic and comprehensive model for measuring the financial health of agricultural companies.…”
Section: Introductionmentioning
confidence: 99%